Predictors of Work Stress among Psychiatric Nursing Staff in Rural and Urban Settings in Taiwan (International Journal of Studies in Nursing, 2017)
Aim: The aim of this study was to compare the work stress of nursing staff in urban and rural areas of Taiwan and to explore the predictors of work stress in nurses in Taiwan. Method: In this cross-sectional study, purposive sampling was adopted to select 271 nursing staff members from 2 psychiatric teaching hospitals. The Emotional Quotient Inventory (Sun, 2004) and the Nurse Stress Checklist (Tsai & Chen, 1996) were used to perform this study. A hierarchical multivariate regression model was used to examine significant predictors of work stress. Results: The work stress of nursing staff in urban hospitals was lower than that of nursing staff in rural hospitals. Compared with the urban nursing staff who participated in the EQ and stress classes, the rural nursing staff, regardless of whether they had attended the classes, experienced more work stress; and hospital types, employment patterns, years of work experience, and emotional intelligence were predictors of work stress. Conclusion: Overall, the findings demonstrate that administration managers must provide effective career advancement measures (eg, offering full-time jobs) or increase salaries to recruit sufficient nursing staff. In addition, managers could avoid unfair treatment experienced by part-time nursing staff by placing additional emphasis on the basic welfares and salaries of nursing staff to effectively mitigate the stress that they experience.